Gastroesophageal reflux in children - Badriul Hegar; Yvan Vandenplas (Paediatrica Indonesiana, 2011)
Gastroesophageal reflux (GER) is the passage of gastric contents into the esophagus and is a normal physiologic process occurring several times per day in healthy individuals. In older children and adolescents, history and physical examination may be sufficient to diagnose gastroesophageal reflux disease (GERD).Endoscopically-visible breaks in the distal esophageal mucosa are the most reliable evidence of reflux esophagitis. Esophageal pH monitoring quantitatively measures esophageal acid exposure. Combined multiple intraluminal impedance and pH monitoring (MII-pH) measures acidic, weakly acidic, non-acidic and gas reflux episodes. MII-pH is superior to pH monitoring alone for evaluation of the temporal relationship between symptoms and GERER. Barium contrast radiography is not useful for the GERERD diagnosis, but may be used to detect anatomic abnormalities. Parental education, guidance, and support are always required and usually sufficient to manage healthy, thriving infants with symptoms likely due to physiologic GERER. Use of a thickened, commercially available anti-regurgitation formula by preference, may decrease visible regurgitation. Buffering agents, alginate and sucralfate, can be beneficial if used as needed for occasional heartburn. Proton-pump inhibitors (PPIs) are superior to histamine-2 receptor antagonists (H2RAs).